(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The publication is devoted to solving the problem of the amnesty of shadow capitals at the global level as an important financial leverage for economy deshadowing. The considerable international experience of conducting economic amnesties as a realization of a certain compromise agreement, which involves the official recognition of the fact of the forced shadow activity implementation, is researched. Compulsory key conditions and potential parameters are proposed that will greatly contribute to the successful implementation of the capital amnesty under the current conditions of the national economy.